Preparation of soybean oil factory sludge catalyst by plasma and the kinetics of selective catalytic oxidation denitrification reaction. (20th April 2019) - Lei, Zhang; Yang, Jia; Lei, Zhang; Huibin, He; Chao, Yang; Min, Luo; Lintian, Miao
Abstract: At present, the treatment of sludge is of great significance for environmental protection. Different from the traditional sewage sludge, in this study sewage sludge from soybean oil factory (named SOF sludge) is firstly used. It is an abandoned solid waste. And it would cause secondary pollution if stacked or incinerated. Therefore, a denitrification catalyst is prepared. The preparation process doesn't produce pollutant emissions. After drying, roasting in the muffle furnace, and decomposing organic matter on the surface, with 15% LiOH (lithium hydroxide) activation and 2% manganese salt incipient impregnation, the sludge catalyst finally was made by plasma; The optimal catalyst was selected under different conditions on roasting power (60 W、90 W、120 W) and roasting time (3 min、5 min、7 min、9 min、11 min), respectively. The characterization of catalyst was analyzed by XPS and XRD, and the activation energy was calculated by the kinetics of SCO (selective catalytic oxidation) denitrification reaction. The results show that: (1) With catalyst the best denitrification performance obtained, the roasting power of the plasma is 90 W and the roasting time is 9 min (2) The activation energy of MnOX /sludge catalyst reaction is 369.16085 kJ/mol. Highlights: The sludge-based catalyst can be prepared as a denitrification catalyst. Plasma roasting can improve the denitrification effect of the catalyst. Activation energy is calculated by the kinetics of denitrification reaction. Denitrification mechanism is analyzed by XPS and XRD characterization.